Variabilidade genética em populações de Hypostomus (Siluriformes : Loricariidae) do Rio Ivaí, Bacia do Alto Rio Paraná, Brasil - Paiva, Suzana de (2006)
The genus Hypostomus shows a complex taxonomy due to a wide variation in its morphology and color pattern what difficult the identification of many species. The isozyme electrophoresis technique was employed to analyse Hypostomus albopunctatus, H. hermanni, H. regani and one morphotype of this genus (Hypostomus sp. 1) from the Ivaí river (Paraná State). The study of nine enzyme systems (AAT, ACP, ADH, EST, GCPDH, G3PDH, LDH, MDH and SOD) allowed the score of 14 loci, some of them being diagnostic for Hypostomus sp. 1 (Adh-A and G3pdh-B), H. hermanni (sAat-B and Gcpdh-A), and H. albopunctatus (Est-2), revealing reproductive isolation between them. Except for H. albopunctatus, which showed zero heterozygosity value (He), the analyzed species showed values above the average for fishes (0.051): 0.126 in Hypostomus sp. 1, 0.199 in H. hermanni, and 0.085 in H. regani. The genetic distance values showed a greater proximity between H. albopunctatus and H. regani (D = 0.218), where as Hypostomus sp. 1 and H. hermanni were the most divergent (D = 0.563). Results pointed out that the analyzed populations show a wide interspecific variation of their gene pool.